PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING PADA RUMAH SAKIT ELIZABETH - Kiswanto, Feri; Karnadi, Karnadi; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study wa to analyze the effect of the variable the influence of leadership and motivation on employee performance througt work discipline as an intervening variables at Elizabeth Situbondo Hospital. By using the Structural equation model of Partial Least Square (PLS). The results of the direct influence hypothesis test using the Smart PLS 3.0 aplication. Leadership has a significant positive effect on Work Discipline, Motivation has a significant positive effect on Work Discipline, Leadership has a significant positive effect on employee performance, Motivation has a positive but not significant effect on employee performance, Work Discipline hal a positive but not significant effect on Employee Performance, Leadership has a positif but nor signifikan effect on Employee Performance througt Work Discipline and Motivation has a significant positive but not signficant effect on Employee performance througt Work Discipline.